The study of psychological traits among Chinese college students during the COVID-19 campus lockdown - Xu, Haibo; Wang, Zhen; Peng, Lixin; Mi, Yanyan; Zeng, Ping; Liu, Xin (Frontiers in Psychology, 2022)
To investigate the prevalence of interpersonal sensitivity, anxiety, depression symptoms and associated risk factors among a large-scale sample of college students in China during the COVID-19 campus lockdown. The survey was conducted among undergraduate students at a university in eastern part of China in April 2022. The Chi-square test was used to compare the different variable groups and multivariable analysis was performed for the risk factors associated with interpersonal sensitivity, anxiety, and depression symptoms. A total of 12,922 college students were included, with an average age of (20.96 ± 1.66) years. The prevalence of interpersonal sensitivity, anxiety and depression symptoms in this study was 58.1, 22.7, and 46.8%, respectively. Male (OR = 1.16, p < 0.001), 22–23 years (OR = 1.40, p < 0.001), freshman (OR = 1.35, p = 0.002), and non-only child (OR = 1.15, p < 0.001) were positively associated with interpersonal sensitivity. Male (OR = 1.20, p < 0.001), sophomores (OR = 1.27, p = 0.020) and seniors (OR = 1.20, p = 0.027) were positively associated with anxiety symptoms. Compared with female students, male students (OR = 0.89, p < 0.001) were less likely to have depression symptoms. 22–23 years (OR = 1.37, p < 0.001), sophomores (OR = 1.26, p = 0.009) and non-only child (OR = 1.11, p = 0.009) were positively associated with depression symptoms. In addition, college students aged 18–21 years, learning status, skipping breakfast, roommate relationship and sleep quality were associated with interpersonal sensitivity, anxiety and depression symptoms (all p < 0.05). The findings of this study suggest a high prevalence of interpersonal sensitivity, anxiety and depression symptoms among Chinese college students during the COVID-19 campus lockdown. Younger ages, low grades, poor dormitory relationship, negative learning status, skipping breakfast and poor sleep quality were the risk factors for college students’ mental health, which should be concerned by the relevant departments of school during the campus lockdown.